Preparation method of cobalt single atom nano-island catalyst and its application in degrading sulfonamide organic pollutants
Through the preparation method of cobalt single-atom nanoisland catalyst, the stability and recycling problems of single-atom catalyst in strong oxidation and acidic reaction environments are solved, and efficient and stable catalytic effect and good anti-interference ability are achieved.
Patent Information
- Application Number
- CN202410699649.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-05-31
AI Technical Summary
The stability problems of existing single-atom catalysts in strong oxidation and acidic reaction environments and recycling problems limit their practical application.
The preparation method of cobalt single-atom nanoisland catalyst is adopted to synthesize zinc acetate and cobalt acetate under hydrothermal conditions to form a nanoisland structure with cobalt atoms dispersed on the surface of zinc oxide, thereby enhancing the thermal stability and recycling ability of the catalyst.
It realizes efficient catalysis under harsh reaction conditions, avoids agglomeration and inactivation of cobalt single atoms during the reaction, has the function of self-regulating the pH of the reaction system, and improves the selectivity and anti-interference ability of the catalyst.
Smart Images

Figure CN118649684B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of antibiotic degradation, and in particular to a method for preparing a cobalt single-atom nano-island catalyst and its application in degrading sulfonamide organic pollutants. Background Art
[0002] As a highly efficient method for degrading organic pollutants, Fenton-like catalytic technology mineralizes organic pollutants by generating highly active free radicals or non-free radicals, showing great application potential.
[0003] Traditional Fenton-like catalysts are usually based on metal nanoparticles. These materials are prone to deactivation and aggregation of active sites during the reaction, resulting in decreased catalytic efficiency and stability. In recent years, single-atom catalysts (SACs) have become a hot topic of research due to their maximized metal atom utilization efficiency and unique catalytic properties. SACs disperse metal atoms in the form of single atoms on a carrier, which not only greatly improves the utilization of metal atoms, but also exhibits catalytic activity and selectivity superior to traditional catalysts due to the unique electronic structure and geometric structure of the single-atom site. Although SACs have shown great potential in catalytic performance, their application in Fenton-like reactions still faces some challenges. First, the stability of single-atom catalysts in strongly oxidizing and acidic reaction environments is particularly prominent, and active metal atoms are easily detached or aggregated from the carrier, resulting in a decrease in catalytic activity. Secondly, the recycling problem of single-atom catalysts is also a key factor limiting their practical application.
[0004] The introduction of single-atom nano-island catalysts provides a new strategy to solve the above problems. Single-atom nano-island catalysts are a new type of catalyst, the core feature of which is the formation of multiple nano-scale islands anchoring single-atom sites on the carrier material. The single atoms are evenly dispersed on the carrier surface without migrating to form agglomerations, so they have highly active catalytic sites. Compared with traditional SACs, single-atom nano-island catalysts not only enhance the thermal stability of the catalyst while maintaining the high activity sites of single atoms, but also avoid agglomeration of atoms under harsh reaction conditions through the strong interaction between nano-islands and single atoms and the special structural design. It also allows the electronic properties of the catalyst to be finely controlled by regulating the interaction between atoms, thereby optimizing the catalytic efficiency and selectivity of specific reactions. In addition, single-atom nano-island catalysts also have an island-sea synergistic effect, and different functions can be achieved by designing the structure of the carrier and the nano-island. In short, this innovative material design concept effectively solves the activity-stability trade-off problem encountered in single-atom catalysts, and provides hope for the efficient and stable treatment of actual difficult-to-degrade pollutant wastewater. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a cobalt single atom nano-island catalyst and its application in degrading sulfonamide organic pollutants, so as to solve the problems existing in the above-mentioned prior art.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] The present invention provides a method for preparing a cobalt single atom nano-island catalyst, comprising the following steps:
[0008] Dissolving zinc acetate and cobalt acetate in a solvent, and adding a base to the system to obtain a viscous precursor solution;
[0009] The obtained precursor solution is subjected to hydrothermal treatment at 150-160° C., and the reaction product is washed and then dried to obtain the cobalt single atom nano-island catalyst.
[0010] As a further preferred embodiment of the present invention, the molar ratio of zinc acetate to cobalt acetate is 0.002-0.004 mol:0.0002-0.0004 mol.
[0011] As a further preferred embodiment of the present invention, the base is potassium hydroxide. More preferably, the mixture is stirred for 6-8 hours after adding potassium hydroxide.
[0012] As a further preference of the present invention, the mass ratio of potassium hydroxide to zinc acetate is 0.224-0.234 g:0.734-0.744 g.
[0013] As a further preferred embodiment of the present invention, the heat treatment time is 20-22 hours.
[0014] As a further preferred embodiment of the present invention, the drying process is carried out at a temperature of 60-80°C and for a time of 6-12 hours. A more preferred drying method is vacuum drying.
[0015] As a further preferred embodiment of the present invention, the solvent is anhydrous ethanol.
[0016] The more preferred cobalt single atom nano-island catalyst preparation process of the present invention is as follows:
[0017] (1) Dissolve 0.634-0.734 g of anhydrous zinc acetate and 0.001-0.005 g of cobalt acetate tetrahydrate in 40-50 ml of anhydrous ethanol and continue stirring;
[0018] (2) adding 40-50 ml of potassium hydroxide solution (0.1-0.2 M) to the solution obtained in step (1), and continuing stirring for 6-8 hours to form a viscous precursor solution;
[0019] (3) transferring the precursor solution obtained in step (2) to a hydrothermal synthesis reactor equipped with a polytetrafluoroethylene liner, and reacting at 150-160° C. for 20-22 h;
[0020] (4) After the reaction is completed, the material is washed with deionized water and ethanol three times each, and then vacuum dried at 60-80° C. for 6-12 hours to obtain a cobalt single atom nano-island catalyst.
[0021] The present invention also provides a cobalt single atom nano-island catalyst prepared by the above preparation method.
[0022] The present invention further provides the use of the above-mentioned cobalt single-atom nano-island catalyst in activating persulfate to degrade sulfonamide organic pollutants.
[0023] As a further preferred embodiment of the present invention, the sulfonamide organic pollutant includes sulfamethoxazole, sulfadiazine, sulfapyridine, sulfathiazole or sulfonamide.
[0024] The cobalt single-atom nano-island catalyst of the present invention is used to activate persulfate to form a Fenton-like system to degrade sulfonamide organic pollutants: first, the single-atom nano-island catalyst is added to a solution of sulfonamide organic pollutants and stirred until the catalyst and the organic pollutant molecules reach an adsorption equilibrium state, and then a persulfate solution is added to react to achieve the degradation of sulfonamide organic pollutants.
[0025] The present invention discloses the following technical effects:
[0026] (1) In the present invention, zinc acetate and cobalt acetate are used as metal precursors, and a nano-island-shaped single-atom dispersed catalyst (Co) in which cobalt single atoms are confined and dispersed on zinc oxide is synthesized by a simple one-step hydrothermal method. SA -ZnO), the unique structural design avoids the aggregation and deactivation of cobalt atoms during the reaction.
[0027] (2) The single-atom nano-island catalyst of the present invention has the function of self-regulating the pH of the reaction system and can maintain a neutral microenvironment of the reaction system. No matter how the initial pH of the system changes within the range of 3 to 8, the pH of the system can be maintained at about 6.4 after the reaction is completed, thereby avoiding the dissolution of metallic cobalt during the reaction.
[0028] (3) The catalyst system of the present invention can efficiently activate peroxymonosulfate in a short time, can generate highly oxidizing sulfate radicals with high selectivity, and can efficiently degrade various sulfonamide organic pollutants (sulfamethoxazole, sulfadiazine, sulfapyridine, sulfathiazole, sulfonamide), and has a strong ability to resist interference from inorganic ions and organic matter, and also has great application potential for treating actual wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 (a) and (b) the X-ray diffraction spectrum of the cobalt single atom nano-island catalyst of Example 1 of the present invention.
[0031] Figure 2 The scanning electron microscope image (a) of the cobalt single atom nano-island catalyst of Example 1 of the present invention and the element content distribution diagram of the "particle-free area" and "particle area" on the catalyst surface (b) are shown.
[0032] Figure 3 This is a high-magnification transmission electron microscope image of the “nano-islands” on the surface of the cobalt single-atom nano-island catalyst in Example 1 of the present invention.
[0033] Figure 4 Among them, (a) is the performance diagram of the degradation of sulfamethoxazole under different reaction conditions of Examples 2-6 of the present invention, (b) is the performance diagram of the degradation of different sulfonamide organic pollutants by activating persulfate with the cobalt single atom nano-island catalyst in Example 7, (c) is the performance diagram of the degradation of sulfamethoxazole by activating persulfate with the cobalt single atom nano-island catalyst in Example 8 under the conditions of different concentrations of inorganic ions, and (d) is the performance diagram of the degradation of sulfamethoxazole by activating persulfate with the cobalt single atom nano-island catalyst in Example 9 under the conditions of different concentrations of humic acid.
[0034] Figure 5 This is a performance diagram of the cobalt single-atom nano-island catalyst in Example 10 of the present invention for activating peroxymonosulfate to degrade sulfamethoxazole solution under different pH conditions.
[0035] Figure 6 This is a diagram showing the change in pH during the process of activating peroxymonosulfate to degrade sulfamethoxazole solutions with different initial pH values using the cobalt single-atom nano-island catalyst in Example 11 of the present invention.
[0036] Figure 7 This is a graph of the amount of metal dissolved after the persulfate degradation reaction using cobalt single atom nano-island catalyst activated by Example 12 of the present invention.
[0037] Figure 8 This is the ESR spectrum of sulfate radicals in the cobalt single atom nano-island catalyst / permonosulfate system of Example 13 of the present invention.
[0038] Fig. 9This is a performance diagram of the cobalt single atom nano-island catalyst / permonosulfate system for continuous treatment of coking wastewater in Example 14 of the present invention.
[0039] Fig.10 This is a performance diagram of the cobalt single atom nano-island catalyst / permonosulfate system cycle experiment of Example 15 of the present invention. DETAILED DESCRIPTION
[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0041] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0042] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0043] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0045] In the following examples of the present invention, the SMX solution is prepared by dissolving SMX in water.
[0046] Example 1
[0047] A method for preparing a cobalt single atom nano-island catalyst:
[0048] (1) Dissolve 0.734 g of anhydrous zinc acetate and 0.005 g of cobalt acetate tetrahydrate in 40 ml of anhydrous ethanol and stir for 1 h;
[0049] (2) Add 40 mL of 0.1 M potassium hydroxide solution to the above solution and continue stirring for 6 h to form a viscous precursor solution;
[0050] (3) transferring the precursor solution to a hydrothermal synthesis reactor equipped with a polytetrafluoroethylene liner and maintaining it at a temperature of 150° C. for 20 h;
[0051] (4) After the reaction, the obtained material was washed with deionized water and ethanol by centrifugation for 3 times, and then vacuum dried at 60°C for 12 h to obtain a cobalt single atom nanoisland catalyst (Co SA -ZnO).
[0052] Example 2
[0053] Cobalt single atom nanoisland catalyst (Co SA -ZnO) activated peroxymonosulfate (PMS) to degrade sulfamethoxazole (SMX):
[0054] Weigh Co using an analytical balance SA -ZnO catalyst 5mg was added to 50mL of SMX solution with a concentration of 10mg / L. The obtained solution was stirred with a magnetic stirrer for 15min to allow the adsorption and desorption equilibrium between the catalyst and the pollutant to be reached, and then 313uL of 80mM permonosulfate solution (PMS) was added to start the timing reaction.
[0055] 1 mL of the sample was taken every 2 minutes for a total of 12 minutes. After sampling, it was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. The sample was placed in a centrifuge and centrifuged at 14,000 rpm for 20 minutes. The supernatant was then injected into a high performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.
[0056] Example 3
[0057] Method for degrading sulfamethoxazole (SMX) by activating peroxymonosulfate (PMS) using ZnO catalyst:
[0058] 5 mg of ZnO catalyst was weighed with an analytical balance and added to 50 mL of 10 mg / L SMX solution. The resulting solution was stirred with a magnetic stirrer for 15 min to allow the catalyst and pollutants to reach adsorption-desorption equilibrium, then 313 uL of 80 mM permonosulfate solution (PMS) was added and the timing reaction was started.
[0059] 1 mL of the sample was taken every 2 minutes for a total of 12 minutes. After sampling, it was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. The sample was placed in a centrifuge and centrifuged at 14,000 rpm for 20 minutes. The supernatant was then injected into a high performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.
[0060] Example 4
[0061] Cobalt single atom nano-island catalyst (Co SA -ZnO) degradation method of sulfamethoxazole (SMX):
[0062] Weigh Co using an analytical balance SA -5 mg of ZnO catalyst was added to 50 mL of SMX solution with a concentration of 10 mg / L. The resulting solution was stirred with a magnetic stirrer for 15 min to allow the catalyst and pollutants to reach adsorption-desorption equilibrium, and then the timing reaction was started.
[0063] 1 mL of the sample was taken every 2 minutes for a total of 12 minutes. After sampling, it was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. The sample was placed in a centrifuge and centrifuged at 14,000 rpm for 20 minutes. The supernatant was then injected into a high performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.
[0064] Example 5
[0065] Method for degrading sulfamethoxazole (SMX) using ZnO alone:
[0066] 5 mg of ZnO catalyst was weighed with an analytical balance and added to 50 mL of 10 mg / L SMX solution. The resulting solution was stirred with a magnetic stirrer for 15 min to allow the catalyst and pollutants to reach adsorption-desorption equilibrium, after which the timing reaction was started.
[0067] 1 mL of the sample was taken every 2 minutes for a total of 12 minutes. After sampling, it was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. The sample was placed in a centrifuge and centrifuged at 14,000 rpm for 20 minutes. The supernatant was then injected into a high performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.
[0068] Example 6
[0069] Method for degrading sulfamethoxazole (SMX) using peroxymonosulfate (PMS) alone:
[0070] 50 mL of 10 mg / L SMX solution was measured and stirred with a magnetic stirrer for 15 min, then 313 uL of 80 mM permonosulfate solution (PMS) was added and the timing reaction was started.
[0071] 1 mL of the sample was taken every 2 minutes for a total of 12 minutes. After sampling, it was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. The sample was placed in a centrifuge and centrifuged at 14,000 rpm for 20 minutes. The supernatant was then injected into a high performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.
[0072] Example 7
[0073] Cobalt single atom nano-island catalyst (Co SA -ZnO) activated peroxymonosulfate (PMS) to degrade different sulfonamide organic pollutants (sulfamethoxazole, sulfadiazine, sulfapyridine, sulfathiazole, sulfonamide):
[0074] Weigh Co using an analytical balance SA 5 mg of ZnO catalyst was added to 50 mL of 10 mg / L sulfamethoxazole, sulfadiazine, sulfapyridine, sulfathiazole, and sulfonamide solutions. The resulting solution was stirred with a magnetic stirrer for 15 minutes to allow the catalyst and pollutants to reach adsorption-desorption equilibrium, and then 313 uL of 80 mM peroxymonosulfate solution (PMS) was added to start the timing reaction.
[0075] 1 mL of the sample was taken every 2 minutes for a total of 12 minutes. After sampling, it was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. The sample was placed in a centrifuge and centrifuged at 14,000 rpm for 20 minutes. The supernatant was then injected into a high performance liquid chromatography to detect the concentration of residual organic pollutants to determine the removal efficiency.
[0076] Example 8
[0077] Method for activating peroxymonosulfate (PMS) to degrade sulfamethoxazole (SMX) using cobalt single atom nanoisland catalysts in the presence of different concentrations of inorganic ions:
[0078] The inorganic ions are chloride ion, nitrate ion, sulfate ion and dihydrogen phosphate ion, and their corresponding drugs are sodium chloride, sodium nitrate, sodium sulfate and sodium dihydrogen phosphate. The addition concentrations are 0mM, 2mM, 5mM and 10mM respectively. The corresponding addition masses of chloride ion (sodium chloride) are 0mg, 5.8mg, 14.6mg and 29.2mg respectively. The corresponding addition masses of nitrate ion (sodium nitrate) are 0mg, 8.5mg, 21.2mg and 42.5mg respectively. The corresponding addition masses of sulfate ion (sodium sulfate) are 0mg, 14.2mg, 35.5mg and 71.0mg respectively. The corresponding addition masses of phosphate ion (sodium dihydrogen phosphate) are 0mg, 12.0mg, 30.0mg and 60.0mg respectively.
[0079] First, weigh the inorganic salt corresponding to the inorganic ion concentration and add it to 50mL of SMX solution with a concentration of 10mg / L. Then weigh 5mg Co SA -ZnO catalyst was added to the above solution and stirred with a magnetic stirrer for 15 minutes to allow the catalyst and the pollutants to reach adsorption-desorption equilibrium, then 313uL of 80mM permonosulfate solution (PMS) was added to start the timing reaction.
[0080] 1 mL of the sample was taken every 2 minutes for a total of 12 minutes. After sampling, it was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. The sample was placed in a centrifuge and centrifuged at 14,000 rpm for 20 minutes. The supernatant was then injected into a high performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.
[0081] Example 9
[0082] Method for activating peroxymonosulfate (PMS) to degrade sulfamethoxazole (SMX) using cobalt single-atom nanoisland catalysts in the presence of different concentrations of organic matter (humic acid):
[0083] The organic matter was humic acid, and the experimental addition concentrations were 0 mg / L, 2 mg / L, 5 mg / L, 10 mg / L, 15 mg / L, and 20 mg / L respectively.
[0084] Preparation of SMX solution (10 mg / L) containing humic acid (0 mg / L): Measure 50 mL of SMX solution (10 mg / L), do not add humic acid solution, and keep the total volume of the solution at 50 mL.
[0085] Preparation of SMX solution (10 mg / L) containing humic acid (2 mg / L): Measure 49.5 mL of SMX solution (10 mg / L), add 0.5 mL of 200 mg / L humic acid solution, and keep the total volume of the solution at 50 mL.
[0086] Preparation of SMX solution (10 mg / L) containing humic acid (5 mg / L): Measure 48.75 mL of SMX solution (10 mg / L), add 1.25 mL of 200 mg / L humic acid solution, and keep the total volume of the solution at 50 mL.
[0087] Preparation of SMX solution (10 mg / L) containing humic acid (10 mg / L): Measure 47.5 mL of SMX solution (10 mg / L), and then add 2.5 mL of 200 mg / L humic acid solution thereto, keeping the total volume of the solution at 50 mL.
[0088] Preparation of SMX solution (10 mg / L) containing humic acid (15 mg / L): Measure 46.25 mL of SMX solution (10 mg / L), add 3.75 mL of 200 mg / L humic acid solution, and keep the total volume of the solution at 50 mL.
[0089] Preparation of SMX solution (10 mg / L) containing humic acid (20 mg / L): Measure 45 mL of SMX solution (10 mg / L), add 5 mL of 200 mg / L humic acid solution, and keep the total volume of the solution at 50 mL.
[0090] Weigh 5 mg Co SA -ZnO catalyst was added to the above prepared solution and stirred with a magnetic stirrer for 15 minutes to allow the catalyst and the pollutants to reach adsorption-desorption equilibrium, then 313uL of 80mM permonosulfate solution (PMS) was added and the timing reaction was started.
[0091] 1 mL of the sample was taken every 2 minutes for a total of 12 minutes. After sampling, it was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. The sample was placed in a centrifuge and centrifuged at 14,000 rpm for 20 minutes. The supernatant was then injected into a high performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.
[0092] Example 10
[0093] Cobalt single atom nanoisland catalysts (Co SA -ZnO) activated peroxymonosulfate (PMS) to degrade sulfamethoxazole (SMX):
[0094] The pH of SMX solution (10 mg / L) was adjusted to 3.0, 5.0, 8.0, and 9.0 using perchloric acid or sodium hydroxide solution. (The pH of normal SMX solution without adding acid or alkali is 6.3). Then, 50 mL of SMX solution with different pH values was measured and 5 mg Co was added. SA -ZnO catalyst was stirred with a magnetic stirrer for 15 min to allow the adsorption-desorption equilibrium between the catalyst and the pollutant to be reached, and then 313 uL of 80 mM permonosulfate solution (PMS) was added to start the timing reaction.
[0095] 1 mL of the sample was taken every 2 minutes for a total of 12 minutes. After sampling, it was added to a test tube containing sodium thiosulfate solution and shaken to terminate the reaction. The sample was placed in a centrifuge and centrifuged at 14,000 rpm for 20 minutes. The supernatant was then injected into a high performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.
[0096] Embodiment 11
[0097] Cobalt single atom nanoisland catalyst (Co SA Method for measuring the pH change of solution during the degradation of sulfamethoxazole (SMX) by peroxymonosulfate (PMS) activated by -ZnO:
[0098] First, use a pH meter to measure the values of SMX solution at different initial pH values, and then add 5 mg Co SA -ZnO catalyst, the detection probe of the pH meter was always submerged in the solution, and the pH value was read after stirring with a magnetic stirrer for 15 minutes. Then 313uL of 80mM permonosulfate solution (PMS) was added, and a value was read every 2 minutes for a total reaction of 12 minutes.
[0099] Example 12
[0100] Cobalt single atom nanoisland catalyst (Co SA Method for measuring the amount of metal ions (cobalt and zinc) released during the degradation of sulfamethoxazole (SMX) by peroxymonosulfate (PMS) activated by ZnO:
[0101] Weigh Co using an analytical balance SA -5mg of ZnO catalyst was added to 50mL of 10mg / L SMX solution. The obtained solution was stirred with a magnetic stirrer for 15min to achieve adsorption-desorption equilibrium between the catalyst and the pollutant, and then 313uL of 80mM permonosulfate solution (PMS) was added to start the timing reaction. After 12min of reaction, the solution was filtered and 10mL of the solution was taken for ICP-OES test to determine the amount of metal ion precipitation.
[0102] Embodiment 13
[0103] Detection method of sulfate radicals in cobalt single atom nano-island catalyst / peroxymonosulfate system:
[0104] 2mg of cobalt single atom nano island catalyst was dispersed in 5mL DMPO aqueous solution and recorded as the first data. 50uL of permonosulfate solution was added separately and dispersed in 5mL DMPO aqueous solution and recorded as the second data. 50uL of permonosulfate solution was added to the dispersion of the above cobalt single atom nano island catalyst and data were collected after 2, 4, and 6 minutes of reaction respectively; 100uL of SMX solution was added to the system and data was collected after 1 minute of reaction.
[0105] Embodiment 14
[0106] Method for continuous treatment of coking wastewater using cobalt single atom nano-island catalyst / permonosulfate system:
[0107] The wastewater source is coking wastewater taken from the factory, and the initial TOC value of the wastewater is 53.35 mg / L. The water body does not contain antibiotics, and the experimental conditions are room temperature (25±2℃), the volume of coking wastewater is 550mL, and the mass of peroxymonosulfate added is 1g.
[0108] First, 300 mg of cobalt single atom nano-island catalyst was weighed and dissolved in water, and then filtered and fixed on the MCE filter membrane. The coking wastewater flowed through the filter membrane containing the catalyst through a peristaltic pump, and the flow rate of the peristaltic pump was 6.08 mL / min. After the coking wastewater stayed on the filter membrane for a period of time, it was pumped into the container under the filter membrane through an external pump. The solution was filtered every 1 hour and its TOC value was measured to determine the TOC removal rate of the experimental system.
[0109] Embodiment 15
[0110] Method for the cyclic experiment of cobalt single atom nano-island catalyst / peroxymonosulfate system:
[0111] Weigh Co using an analytical balance SA-5mg of ZnO catalyst was added to 50mL of SMX solution with a concentration of 10mg / L. The obtained solution was stirred with a magnetic stirrer for 15min to achieve adsorption and desorption equilibrium between the catalyst and the pollutant, and then 313uL of permonosulfate solution (PMS) with a concentration of 80mM was added to start the timing reaction. After 12min of reaction, 1mL of sample was taken, and then added to a test tube with sodium thiosulfate solution, and shaken to terminate the reaction. After 12min of reaction, SMX has been completely degraded. Then a certain amount of 200mg / L of SMX solution was diluted to the solution after the above reaction, and the solution concentration was continued to be maintained at 10mg / L, and then 313uL of permonosulfate solution (PMS) with a concentration of 80mM was added, and the timing reaction was continued. After the reaction, 1mL of sample was taken, and then added to a test tube with sodium thiosulfate solution, and shaken to terminate the reaction. The above operation was repeated ten times, for a total of ten cycles. Finally, the samples after ten cycles were placed in a centrifuge and centrifuged at 14,000 rpm for 20 min. The supernatant was then injected into a high-performance liquid chromatography to detect the residual SMX concentration to determine the removal efficiency.
[0112] Figure 1 (a) and (b) the X-ray diffraction spectrum of the cobalt single atom nano-island catalyst prepared in Example 1 of the present invention.
[0113] from Figure 1 (a) It can be seen that the introduction of cobalt did not destroy the phase structure of zinc oxide, and no other diffraction peaks related to cobalt appeared, indicating that the cobalt single atom catalyst was successfully synthesized. Figure 1 As can be seen in (b), compared with the Co-Co bonds in Co foil and the Co-Co bonds in CoO, the Co in the cobalt single atom nanoisland catalyst only presents Co-Zn and Co-O bonds, which strongly proves that the Co in the catalyst presents a single atom distribution and is coordinated with Zn and O without the formation of clusters and nanoparticles.
[0114] Figure 2 The scanning electron microscope image (a) of the cobalt single atom nano-island catalyst prepared in Example 1 of the present invention and the element content distribution diagram of the "particle-free area" and "particle area" on the catalyst surface (b).
[0115] Depend on Figure 2 (a) It can be seen that zinc oxide presents a regular octahedral structure, and many small particles are dispersed on its surface. Figure 2 (b) It can be seen that no Co element signal was detected at the “particle-free area” of the zinc oxide surface of the catalyst, while an obvious Co element signal (5.7wt%) was detected at the particles, which strongly proves that Co atoms are distributed on the “nano-islands” of zinc oxide surface particles.
[0116] Figure 3 This is a high-magnification transmission electron microscope image of the "nano island" on the surface of the cobalt single-atom nano-island catalyst prepared in Example 1 of the present invention. Figure 3 It can be seen that the lattice fringes are clear, and the 0.28 nm lattice fringes correspond to the (100) crystal plane of zinc oxide, proving that the "particles" on the surface of zinc oxide are zinc oxide.
[0117] Figure 4 (a) is a performance diagram of the degradation of sulfamethoxazole under different reaction conditions in Examples 2-6. It can be seen that sulfamethoxazole is hardly removed in the presence of PMS alone, indicating that PMS alone is not able to oxidatively degrade sulfamethoxazole. In addition, sulfamethoxazole is hardly removed in the presence of zinc oxide and cobalt single-atom nano-island catalysts alone, indicating that their adsorption contribution is negligible. Zinc oxide catalyst activates PMS within 12 minutes to achieve a degradation rate of 16.4% for sulfamethoxazole. The efficiency of activating PMS to degrade sulfamethoxazole by cobalt single-atom nano-island catalysts within 12 minutes can reach 100%. Figure 4 (b) is a graph showing the degradation and removal of different sulfonamide-containing organic pollutants by the cobalt single atom nanoisland catalyst / permonosulfate system in Example 7. The concentration of each pollutant is 10 mg / L. As can be seen from the graph, the system has a good degradation ability for these pollutants and can almost completely remove them within 12 minutes.
[0118] Figure 4 (c) and 4 (d) are the degradation performance diagrams of sulfamethoxazole by the system in the presence of different concentrations of inorganic ions and natural organic matter (humic acid) in Examples 8-9. As can be seen from the figure, the presence of complex anions and natural organic macromolecules does not interfere with the degradation and removal of sulfamethoxazole by the system. This group of experimental results shows that the cobalt single atom nano-island catalyst / permonosulfate system is suitable for the purification of actual complex water bodies.
[0119] Figure 5 The performance diagram of the cobalt single atom nano island catalyst activating peroxymonosulfate to degrade sulfamethoxazole under different pH conditions in Example 10. It can be seen from the figure that even under acid or alkaline conditions, the cobalt single atom nano island catalyst / peroxymonosulfate system can still efficiently degrade sulfamethoxazole. This group of experiments proves that the prepared cobalt single atom nano island catalyst can still maintain good stability and catalytic activity in different acid-base reaction environments.
[0120] Figure 6The figure is a diagram showing the change of pH of the cobalt single-atom nano-island catalyst in the process of activating persulfate to degrade sulfamethoxazole solutions with different initial pH values in Example 11. As can be seen from the figure, no matter how the initial pH of the sulfamethoxazole solution changes within the range of 3 to 8, the cobalt single-atom nano-island catalyst can stabilize the pH value of the system solution at about 6.4, which indicates that the cobalt single-atom nano-island catalyst has the function of adjusting the pH of the solution and can maintain the neutral microenvironment of the system.
[0121] Figure 7 This is a graph of the amount of metal dissolved after the persulfate degradation reaction of sulfamethoxazole activated by the cobalt single atom nano-island catalyst in Example 12. It can be seen that the amount of cobalt dissolved after the reaction is 0, which further illustrates that the self-stabilizing pH function of the cobalt single atom nano-island catalyst can effectively avoid the dissolution of metal cobalt.
[0122] Figure 8 The ESR spectrum of sulfate radicals in the cobalt single atom nano island catalyst / permonosulfate system in Example 13. As can be seen from the figure, after the catalyst reacts with the oxidant, the sulfate radical shows a strong spectrum signal, and the signal intensity gradually increases with the extension of the reaction time, indicating that the single atom nano island catalyst can efficiently activate permonosulfate in a short time, and highly selectively generate highly oxidizing sulfate radicals, thereby efficiently degrading various organic pollutants.
[0123] Fig. 9 This is a performance diagram of the cobalt single atom nano-island catalyst / permonosulfate system continuously treating coking wastewater in Example 14. As can be seen from the figure, the system has a good effect on TOC removal of coking wastewater, and can still achieve a removal rate of 48% after continuous treatment for 12 hours. This shows that the system has a good ability to treat actual wastewater.
[0124] Fig.10 This is the performance diagram of the cobalt single atom nano-island catalyst / peroxymonosulfate system cycle experiment in Example 15. As can be seen from the figure, the system has good cycle stability, and can still achieve nearly 90% degradation efficiency after ten cycles. This shows that the cobalt single atom nano-island catalyst prepared by this system has good structural stability, overcoming the bottleneck problem of poor cycle effect of traditional single atom catalysts.
[0125] The present invention uses zinc acetate and cobalt acetate as metal precursors, utilizes potassium hydroxide as an alkali source, and disperses cobalt atoms on various "nano-islands" on the surface of zinc oxide through a one-step hydrothermal method. The prepared catalyst activates permonosulfate to degrade and remove sulfonamide organic pollutants in water.
[0126] The single-atom nano-island catalyst of the present invention has the function of self-regulating the pH of the reaction system, can maintain the neutral microenvironment of the reaction system, and avoid the dissolution of metal cobalt during the reaction. In addition, the single-atom nano-island catalyst system can efficiently activate peroxymonosulfate in a short time, highly selectively generate highly oxidizing sulfate radicals, and efficiently degrade various sulfonamide organic pollutants. It also has a strong ability to resist interference from inorganic ions and organic matter, and has great application potential for treating actual wastewater.
[0127] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a cobalt single atom nano-island catalyst, characterized in that: The following steps are involved: Dissolve zinc acetate and cobalt acetate in ethanol at a molar ratio of 0.002-0.004 mol:0.0002-0.0004 mol, add potassium hydroxide to the system and stir for 6-8 hours to obtain a precursor solution; The precursor solution is reacted at 150-160° C. for 20-22 hours, and then dried to obtain the cobalt single atom nano-island catalyst; Among them, the mass ratio of potassium hydroxide to zinc acetate is 0.224-0.234 g:0.734-0.744 g.
2. The method for preparing the cobalt single atom nano-island catalyst according to claim 1, characterized in that: The drying process is carried out at a temperature of 60-80°C and for a time of 6-12 hours.
3. The cobalt single atom nano-island catalyst prepared by the preparation method according to any one of claims 1 to 2.
4. Use of the cobalt single atom nano-island catalyst as claimed in claim 3 in activating persulfate to degrade sulfonamide organic pollutants.
5. The use according to claim 4, characterized in that: The sulfonamide organic pollutants include one or more of sulfamethoxazole, sulfadiazine, sulfapyridine, sulfathiazole and sulfonamide.
Citation Information
Patent Citations
Preparation method of molecular pollution adsorption material with carbon black coated with ZnO film layer and adsorption device
CN110801810A
Method for degrading organic pollutants in water by using nitrogen-doped porous carbon anchored monatomic cobalt catalyst to activate persulfate
CN112408577A